Training in making tea bags from Cherry leaves to foster entrepreneurial creativity with PKK women in Krandon village, Demak - Alvania Nabila Tasyakuranti; Wardatul Bahiyyah; Teguh Wibowo (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2024)
KKN students of Universitas Islam Negeri Walisongo Semarang held a cherry leaf tea-making activity with PKK women in Krandon village. Using cherry leaves to make tea bags is a creative idea from the students that can be applied in the health sector and as an entrepreneurial idea independently carried out by the community. This initiative is motivated by the fact that most of the population has high blood sugar, cholesterol, and uric acid levels. The primary purpose of this training is to socialize the health benefits of cherry leaves and provide entrepreneurial ideas for selling herbal tea bags from cherry leaves that can be made more attractive and have high selling value. The results of the cherry leaf tea-making training activities have positively impacted the people of Krandon village. Firstly, it can provide information about the benefits of cherry leaves that were previously unknown to the public. Previously, people only used the fruit without knowing that cherry leaves can also be used for health and as an entrepreneurial idea. Secondly, it motivates women to develop the use of cherry leaves as a selling idea. Thirdly, it can produce tea bags from leaves found in many places and substitute other herbal teas.